2022
DOI: 10.3390/jcm11216390
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coexisting Gestational Diabetes Mellitus on the Course of Preeclampsia

Abstract: A strict correlation between gestational diabetes mellitus (GDM) and preeclampsia (PE) has been shown in previous studies. This case-control observational study evaluates the influence of concomitant GDM on the severity of PE. Ninety-nine patients were included: thirty-eight with PE without GDM (group 1), fourteen with PE and concomitant GDM (group 2), and forty-seven with uncomplicated pregnancies (group 3). Adverse maternal/fetal and neonatal outcomes were registered. Patients underwent blood sample analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…First, differences in the metabolic profiles of patients with and without GDM may have affected the findings. Second, although the independent and significant associations between GDM and PE have been confirmed, the main mechanistic manifestations are completely different GDM is a proangiogenic state and PE is an antiangiogenic state [27] . This may affect the association between quercetin and these two diseases.…”
Section: Resultsmentioning
confidence: 97%
“…First, differences in the metabolic profiles of patients with and without GDM may have affected the findings. Second, although the independent and significant associations between GDM and PE have been confirmed, the main mechanistic manifestations are completely different GDM is a proangiogenic state and PE is an antiangiogenic state [27] . This may affect the association between quercetin and these two diseases.…”
Section: Resultsmentioning
confidence: 97%
“…This suggest that absence of AM2 function renders increased risk for metabolic disorder under stressful conditions such as establishment of pregnancy. Preeclampsia (PE) and gestational diabetes mellitus (GDM) are common pregnancy complications, occurring only during pregnancy with similar risk factors and patho-physiological changes (Pankiewicz et al, 2022;Yang and Wu, 2022). Evidence from previous studies suggests that the incidence of PE is significantly increased in women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-related PE is known to be associated with GDM, and numerous investigations have established a clear link between these two conditions. 8 The study revealed that women diagnosed with GDM are at a greater risk of getting preeclampsia compared to those who do not have GDM. They proposed that the elevated blood sugar levels and reduced responsiveness to insulin seen in gestational diabetes mellitus (GDM) might potentially contribute to impaired functioning of the endothelium, a characteristic feature of preeclampsia.…”
Section: Introductionmentioning
confidence: 96%